Comparison of dosimetry in head and neck cancer patients treated with intensity modulated radiation therapy and helical tomotherapy - B. R., Yashaswini; Swamy, Kumara (International Journal of Research in Medical Sciences, 2021)
Background: This study was conducted to compare dosimetric parameters and dose to specific organs at risk (spinal cord and parotids) between intensity modulated radiation therapy (IMRT) and helical tomotherapy (HT) in head and neck squamous cell carcinomas (HNSCC). Methods: Thirty patients with histologically proven HNSCC were treated with chemo radiotherapy, to a dose of 60-70 Gray in 30-35 fractions. This study consists of two arms; IMRT arm and tomotherapy arm. Fifteen consecutive patients treated under IMRT and 15 patients were treated under helical tomotherapy, along with concurrent chemotherapy. PTV1 encompasses low risk planning target volume (PTV) which receives 50 Gy; PTV2 encompasses intermediate risk PTV which receives 54-60 Gy and PTV3 encompasses high risk PTV which receives 66-70 Gy. After completion of planning, dose to the organs at risk (OARs) and targets, homogeneity index and conformity index were evaluated, and tabulated. Results: On evaluation of plans we found that V95% in PTV1, PTV2 and PTV3 were 91.82%, 96.85% and 90.67% respectively for IMRT and 99.25%, 99.68% and 99.73% respectively for tomotherapy. For PTV3, V110% was 0.11% for IMRT and 0.01% for tomotherapy. Homogeneity index in IMRT arm was 0.285 and it was 0.206 in tomotherapy arm. Conformity index was found to be 1.04 for IMRT plans and 1.06 for tomotherapy plans. When mean dose to contra lateral parotids was evaluated, it was 26.91 Gy in IMRT arm and 25.97 Gy in tomotherapy arm. Max dose to spinal cord was better in tomotherapy (43.07 Gy in IMRT and 34.41 Gy in tomotherapy). Conclusions: There was statistically significant reduction in spinal cord maximum dose and point doses in tomotherapy plans compared to IMRT plans. The decrease in spinal cord dose can increase the tolerance reserve which can be useful in dose escalation or re-irradiation if required. There was also decrease in contra lateral parotid doses (not statistically significant). There was significant improvement in V95% in tomotherapy arm compared to IMRT arm, indicating the significantly superior coverage of target volumes in helical tomotherapy plans compared to IMRT plans. V110% (hot spots) inside the target was very minimal in tomotherapy arm compared to IMRT arm. Conformity index, homogeneity index between two arms were comparable.